The Impact of Colonialism to Pandora Society in James Cameron’s Film Avatar The Way of Water 2022 - Rasifa (English Language, Linguistics, Literature, And Education Journal, 2025)
This research aims to analyze the causes and impacts of colonialism on the Pandora society in James Cameron's film Avatar: The Way of Water. The study employs a literary sociology approach with a qualitative descriptive method, allowing the researcher to explore the relationship between social structures and the film's narrative. The main theoretical frameworks used include Miftakhuddin’s theory of colonialism and Ziltener & Künzler’s framework on the impacts of colonialism. Data were collected through documentation techniques and analyzed based on categories of colonial causes (economic, political, socio-cultural, and technological) and their impacts (political, economic, socio-cultural, and environmental). The findings reveal that colonialism in the film is depicted through natural resource exploitation, military domination over local political structures, cultural erosion and identity loss among indigenous communities, and the use of advanced technology as a tool of domination. The film symbolically reflects real-world colonial dynamics and offers a critique of the exploitative practices and erasure of local identities by imperialist powers